Factors that affect customer satisfaction at PT Madani Primatama Logistik - Binton Siburian; Annisa Agustina; Parlin Tumpal Sinaga; Kuncu Saragih; Johan Hursepuny (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2023)
This study was conducted to determine the factors that affect customer satisfaction at PT Madani Primatama Logistic. The variables studied were the variables of Location (X1), Trust (X2), Sense of Security (X3) and Customer Satisfaction (Y). The type of research used is descriptive quantitative. The data collection technique used is a questionnaire or questionnaire. Furthermore, the sampling technique used is purposive sampling technique with a total of 100 respondents. The results of this study indicate that location and sense of security have no effect on customer satisfaction of PT Madani Primatama Logistik, while trust affects customer satisfaction of PT Madani Primatama Logistik. Simultaneously location, trust and a sense of security have no effect on customer satisfaction of PT Madani Primatama Logistik.